The influence of communication modality and shared visual information on collaboration in virtual teams - Saikayasit, Rossukorn (2011)
The rise of the internet coupled with advancements in computing technology has contributed to the increasing popularity of virtual team working. Virtual teams rely heavily upon the use of mediated communication as face-to-face interaction is limited. Many off-the-shelf collaborative technologies with multiple features are widely accessible in the market to support virtual collaboration. These technologies are being adopted to support uni- and multi-modal interaction in various workplace settings. However the influence of these technologies is often domain specific and is dependent on the type of tasks and teams, thus selecting the most appropriate tool to support a specific collaborative task is difficult.